Liquidity and Solvency PT Electronic City Indonesia Tbk for the Period of 2016-2019 - Radna Nurmalina; Mufrida Zein; Yuli Fitriyani; Tri Atmini Rahayu (International Journal of Research in Vocational Studies (IJRVOCAS), 2022)
This study aims to determine the company's financial performance in fulfilling short-term and long-term obligations of the company PT Electronic City Indonesia Tbk. The analytical technique used in this research is quantitative analysis. The data used in this study is in the form of the financial statements of the company PT Electronic City Indonesia Tbk for the period 2016-2019 which is measured using the liquidity ratio and solvency ratio. The results of the analysis on the level of liquidity in terms of the Current Ratio, the ratio is above the industry standard so the company is in good condition. Judging from Quick Ratio, the ratio has increased from below the industry standard to above the industry standard. Judging from the Cash Ratio, the ratio numbers have increased and decreased, so that at a certain period the company was in a bad condition, namely in 2018 the cash owned by the company decreased. Judging from the cash turnover ratio, the ratio is below the industry standard, so the company's financial performance is in good condition because the smaller the ratio, the better for the company. in terms of Inventory to Net Working, the ratio is above the industry standard, although it decreases every period. The results of the analysis on the level of solvency in terms of the Dept. To Equity Ratio, the ratio is below the industry standard, which indicates that the condition of the company is in good condition, because the smaller the ratio, the better for the company. Judging from the Dept. To Asset Ratio, the ratio is below the industry standard, which means the company is in good condition. Judging from Long Term to Equity Ratio, the ratio is below the industry standard, which means the company is in good condition. Judging from the Tangible Assets Debt Coverage, it shows that the company's condition is in good condition because the total long-term debt can be repaid with intangible fixed assets owned by the company, based on the results of effective solvency, the company's financial performance can be said to be good.